Search for neutral Higgs bosons of the minimal supersymmetric standard model decaying to tau pairs in pp collisions at square root of s = 1.96 TeV. - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
We present a search for neutral supersymmetric Higgs bosons decaying to tau pairs produced in pp collisions at square root of s = 1.96 TeV. The data, corresponding to 310 pb(-1) integrated luminosity, were collected with the Collider Detector at Fermilab in run II of the Tevatron. No significant excess above the standard model backgrounds is observed. We set exclusion limits on the production cross section times branching fraction to tau pairs for Higgs boson masses in the range from 90 to 250 GeV/c2.